POD1UM-303/InterAACT 2: A phase III, global, randomized, double-blind study of retifanlimab or placebo plus carboplatin–paclitaxel in patients with locally advanced or metastatic squamous cell anal carcinoma - Rao, Sheela; Jones, Mark; Bowman, Jill; Tian, Chuan; Spano, Jean-Philippe (Frontiers in Oncology, 2022)
Background Squamous carcinoma of the anal canal (SCAC) is a human papillomavirus (HPV)-driven cancer with poor prognosis in locally advanced or recurrent settings. Carboplatin–paclitaxel is the preferred first-line regimen for unresectable locally advanced or metastatic SCAC, with the reported median progression-free survival (PFS) and overall survival (OS) of 8.1 and 20.0 months, respectively. Immune checkpoint blockade (ICB) demonstrates improved survival in HPV-driven cervical and head and neck cancers. Retifanlimab (INCMGA00012) is an investigational humanized, hinge-stabilized, immunoglobulin G4κ monoclonal antibody targeting programmed cell death-1 (PD-1), with characteristics common to the ICB class. In POD1UM-202, retifanlimab showed substantial clinical activity and an expected safety profile in patients with advanced SCAC who progressed on platinum-based chemotherapy. Based on these encouraging results, POD1UM-303/InterAACT 2 (NCT04472429), a phase III, double-blind, randomized, multiregional study, investigates the addition of retifanlimab to the standard of care (SOC) carboplatin–paclitaxel in patients with inoperable locally recurrent or metastatic SCAC not previously treated with systemic chemotherapy. Methods and analysis Patients ≥18 years with inoperable locally recurrent or metastatic SCAC, measurable disease per RECIST v1.1, and no prior systemic chemotherapy or PD-(L)1-directed therapy will be enrolled and stratified by PD-L1 expression, region, and extent of disease. Patients with well-controlled human immunodeficiency virus infection are eligible. Planned enrollment is approximately 300 patients worldwide, with a 1:1 randomization to retifanlimab or placebo. Patients will receive up to six induction cycles (24 weeks) of carboplatin (area-under-the-curve 5 on day 1) and paclitaxel (80 mg/m2 on days 1, 8, and 15) every 28 days per SOC. Concurrently, retifanlimab 500 mg or placebo will be administered intravenously in a blinded fashion on day 1 of each 28-day cycle for up to 13 cycles (1 year) in the absence of unacceptable toxicity, disease progression, withdrawal of consent, loss to follow-up, or premature discontinuation. Crossover to open-label retifanlimab will be allowed for patients assigned to placebo upon verification of progression by blinded independent central radiographic review (BICR). The primary study endpoint is PFS per RECIST v1.1 by BICR. Secondary endpoints are OS, objective response rate, duration of response, disease control rate, safety, and retifanlimab pharmacokinetics. The study is currently recruiting. Clinical Trial Registration https://clinicaltrials.gov/ct2/show/NCT04472429; https://clinicaltrialsregister.eu/ctr-search/search?query=2020-000826-24